Comparison of Actigraphy with Polysomnography and Sleep Logs in Depressed Insomniacs - McCall, Catherine (2011)
Actigraphy is increasingly used in the assessment and treatment of various clinical conditions, being a convenient and cost-effective method of capturing bodily movements over long periods of time. This study examined the use of actigraphy in the measurement of sleep of patients with depression and insomnia. Fifty four patients diagnosed with a current major depressive episode and chronic insomnia underwent a baseline overnight study with concurrent actigraphic and polysomnography (PSG) monitoring, as well as subjective sleep diaries. Agreement between PSG, actigraphy and sleep diary measurements was evaluated using two-tailed t-tests, Pearson’s correlations, and the Bland-Altman concordance technique. The only significant difference found between actigraphy and PSG was in latency to persistent sleep, in which actigraphy underestimated sleep latency relative to PSG (p<0.05). There were moderate positive correlations between actigraphy and PSG for all variables. In contrast, significant differences were observed between sleep diaries and PSG for all sleep variables. Bland-Altman concordance diagrams also demonstrated that, while bias was limited between PSG and the other two measurement types, there were somewhat broad 95% limits of agreement for all sleep variables with both sleep diaries and actigraphy. In summary, actigraphic measurements of sleep more closely approximated those of PSG than did sleep diaries in this sample of depressed insomniacs.